2007
DOI: 10.1176/appi.ajp.164.6.936
|View full text |Cite
|
Sign up to set email alerts
|

Therapist Affect Focus and Patient Outcomes in Psychodynamic Psychotherapy: A Meta-Analysis

Abstract: These data indicate that therapist facilitation of patient affective experience/expression is associated with patient improvement over the course of psychodynamic psychotherapy. Although the size of this relationship was not significantly related to methodological quality, results suggest the importance of close supervision of actual techniques through the use of audio- or videotapes. Additionally, results highlight the importance of defining outcome in a multidimensional way to properly assess theoretically r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
35
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 0 publications
9
35
2
1
Order By: Relevance
“…Furthermore, the use of video playback can enable greater specificity in guiding the timing and application of therapeutic technique, providing anchored instruction (Binder, 2004). This is consistent with the finding that use of Studies included in the 6 select reviews of Psychodynamic therapy: Abbass (2006) -23 studies Abbass (2009) -14 studies Diener (2007) -10 studies Driessen (2010) -23 studies -10 studies Town (2011) -7 studies 71 independent studies idenƟfied through a manual review of 6 prior reviews (excluding 16 duplicate studies included in 2 or more reviews) 30 excluded studies-reasons for exclusion: 23 studies-Criterion of randomized design not fulfilled 7 studies-Study data unavailable 41 independent studies consisƟng of 46 treatment arms met inclusion criteria and were included in meta-analysis Figure 1. Process of selection of trials.…”
Section: Audio/video Recording In Psychodynamic Psychotherapysupporting
confidence: 85%
“…Furthermore, the use of video playback can enable greater specificity in guiding the timing and application of therapeutic technique, providing anchored instruction (Binder, 2004). This is consistent with the finding that use of Studies included in the 6 select reviews of Psychodynamic therapy: Abbass (2006) -23 studies Abbass (2009) -14 studies Diener (2007) -10 studies Driessen (2010) -23 studies -10 studies Town (2011) -7 studies 71 independent studies idenƟfied through a manual review of 6 prior reviews (excluding 16 duplicate studies included in 2 or more reviews) 30 excluded studies-reasons for exclusion: 23 studies-Criterion of randomized design not fulfilled 7 studies-Study data unavailable 41 independent studies consisƟng of 46 treatment arms met inclusion criteria and were included in meta-analysis Figure 1. Process of selection of trials.…”
Section: Audio/video Recording In Psychodynamic Psychotherapysupporting
confidence: 85%
“…Indeed, a meta-analysis including 10 STPP studies found that therapist facilitation of affect was positively associated with treatment improvement (Diener, Hilsenroth, & Weinberger, 2007). The demonstration of an association between specific therapist technique in STPP and patient improvement is evidence supporting the treatments effectiveness but further research is required to establish if this relationship is mediated by emotional processing.…”
mentioning
confidence: 99%
“…Other empirical studies have also demonstrated links between psychodynamic methods and successful outcome, whether or not the investigators explicitly identified the methods as "psychodynamic" (e.g., Barber, Crits-Christoph, & Luborsky, 1996;Diener, Hilsenroth, & Weinberger, 2007;Gaston, Thompson, Gallagher, Cournoyer, & 11 See the original source for more complete descriptions of the two therapy prototypes (Ablon & Jones, 1998). 12 The study is one of the archival studies analyzed by Jones and his associates (Ablon & Jones, 1998;Jones & Pulos, 1993).…”
mentioning
confidence: 99%